Emotional quotient vs. intelligence quotient to achieve professional excellence in life: a systematic literature review - Srivastava, Manushi; Jaiswal, Shweta (International Journal Of Community Medicine And Public Health, 2022)
In the last few decades, the concept of emotional quotient has received more considerable attention than intelligence quotient. In fact, emotional quotient was projected as a solution to a myriad of problems faced in work, education and health domains. This is so because high EQ helps to build relationships, reduce team stress, defuse conflict and improve job satisfaction. The present study is based on systematic literature review with the aim to assess importance of EQ in achieving professional excellence in life. The search span was from year 1990-2020. A total of 60 research articles were excluded and 659 records were screened at this stage. Finally, after screening and eligibility process 10 studies included in data extraction. According to available literature, previous researchers assumed that having a high IQ ensured success in professional life, but people are now struggling miserably in the workplace, despite having a high IQ and excellent analytical skills. Later, it was realised that IQ alone does not guarantee success in life. Therefore, EQ becomes a best predictor of the success and now researchers are focusing on the emotional aspect which helps an individual to be sensitive about his/her emotions as well as the emotions of others. Through the EQ a person builds up the ability in the self-adaptation for solving the pressure of life in the competing status of an individual and enhancing communication and decision-making power. The important aspect about emotional quotient is that, unlike IQ, it can be improved throughout life.